To solve the given system of equations, we will translate the equations and arrange them systematically.
The equations given are:
- \( x - y - 8z = -81 \) (Equation 1)
- \( y + 5z = 47 \) (Equation 2)
- \( 6y + 7z = 52 \) (Equation 3)
Let's solve this system step-by-step:
Step 1: Solve Equation 2 for \( y \).
From Equation 2:
\[ y = 47 - 5z \]
Step 2: Substitute \( y \) in Equations 1 and 3.
For Equation 1:
\[ x - (47 - 5z) - 8z = -81 \]
Simplifying this gives:
\[ x - 47 + 5z - 8z = -81 \] \[ x - 47 - 3z = -81 \] \[ x - 3z = -81 + 47 \] \[ x - 3z = -34 \] \[ x = -34 + 3z \quad \text{(Equation 4)} \]
For Equation 3:
Now substitute \( y = 47 - 5z \) into Equation 3:
\[ 6(47 - 5z) + 7z = 52 \] \[ 282 - 30z + 7z = 52 \] \[ 282 - 23z = 52 \] \[ -23z = 52 - 282 \] \[ -23z = -230 \] \[ z = 10 \]
Step 3: Substitute \( z \) back to find \( y \) and \( x \).
Now substitute \( z = 10 \) back into Equation 2 to find \( y \):
\[ y = 47 - 5(10) = 47 - 50 = -3 \]
Now substitute \( y \) and \( z \) into Equation 4 to find \( x \):
\[ x = -34 + 3(10) = -34 + 30 = -4 \]
Final Solution:
We find:
\[ x = -4, \quad y = -3, \quad z = 10 \]
Thus, the one solution is:
A. The one solution is \( x = -4 \), \( y = -3 \), and \( z = 10 \).